Dissociation and post-traumatic stress disorder: two prospective studies of road traffic accident survivors. - Murray, J; Ehlers, A; Mayou, R (2002)
BACKGROUND: Dissociative symptoms during trauma predict post-traumatic stress disorder (PTSD), but they are often transient. It is controversial whether they predict chronic PTSD over and above what can be predicted from other post-trauma symptoms. AIMS: To investigate prospectively the relationship between dissociative symptoms before, during and after a trauma and other psychological predictors, and chronic PTSD. METHOD: Two samples of 27 and 176 road traffic accident survivors were recruited. Patients were assessed shortly after the accident and followed at intervals over the next 6 months. Assessments included measures of dissociation, memory fragmentation, data-driven processing, rumination and PTSD symptoms. RESULTS: All measures of dissociation, particularly persistent dissociation 4 weeks after the accident, predicted chronic PTSD severity at 6 months. Dissociative symptoms predicted subsequent PTSD over and above the other PTSD symptom clusters. Memory fragmentation and data-driven processing also predicted PTSD. Rumination about the accident was among the strongest predictors of subsequent PTSD symptoms. CONCLUSIONS: Persistent dissociation and rumination 4 weeks after trauma are more useful in identifying those patients who are likely to develop chronic PTSD than initial reactions.